Potential for Peacebuilding in Conflict and Violence in Sri Lanka Based on the Thoughts of Johan Galtung - Galbani Fadilah; Ilim Abdul Halim (Gunung Djati Conference Series, 2021)
This study aims to discuss the conflicts and violence that occurred in Sri Lanka and the potential for peace based on the thoughts of Johan Galtung. This research method is qualitative through literature study. The results and discussion of this study show that the theory of conflict and violence initiated by Johan Galtung is linear and can be applied to problems in Sri Lanka. This study concludes that the conflict resolution initiated by Johan Galtung opens up the potential for peacebuilding, which can then be applied to the problems of conflict and violence in Sri Lanka.